RADIONUCLIDE IMAGING OF NEUROENDOCRINE TUMORS - petrović, Jelena; Macut, Djuro; Šobić Šaranović, Dragana (Medicinski podmladak, 2020)
Neuroendocrine tumors (NETs) are relatively rare and heterogeneous with a very variable clinical expression and progression. They derive from the sensory and secretory neuroendocrine cells mainly within the pulmonary and gastrointestinal tract.  They comprise less than 2% of all malignancies. On the basis of clinical behavior, histology, and proliferation rate, they are devided into well differentiated (low grade to intermediate grade) and poorly differentiated (high grade) neuroendocrine carcinoma. Belonging to each of these categories  has impact on treatment and prognosis. The only curative treatment is surgery. Considering that more than 50% of the patients present metastatic disease at the time of diagnosis, the systemic treatment must be included such as chemotherapy and targeted agents, as well as peptide receptor radiotherapy. For the diagnosis and follow-up of these tumors various radiological methods are used (computed tomography, magnetic resonance imaging, ultrasound) as well as endoscopy. Nuclear medicine methods are used in order to exploit their unique properties mainly amine precursor uptake and decarboxylation system characteristics as well as the expression of somatostatin receptors. These procedures offers a total body examination and a better staging of the disease. Imaging can be performed with gamma camera (SPECT, SPECT/CT)  or positron emission tomography (PET/CT). Radiopharmaceuticals used for imaging with gamma camera are usually  99mTc-(V)-DMSA, 99mTc- MIBI, 99mTc-HYNIC TOC, 111In-pentetreotide and 131I-MIBG/123I-MIBG. Positron emitting radiopharmaceuticals has superior spatial resolution and faster imaging, such as 68Ga-DOTA-somatostatin analogues, 18FDG ( particularly for high-grade tumors), 18F-L-DOPA/11C-L-DOPA and 11C-5-hydroxytryptophan and have demonstrated excellent imaging results. The new targeted agents present a challenge in the evaluation procedure of treatment and, therefore, new imaging techniques and an improvement of currently available techniques are mandatory. In this mini-review, the most frequent methods and technologijes are presented as well as potential development.
Keywords: neuroendocrine tumors, positrón emission tomography, gamma camera, radiopharmaceuticals